2020
DOI: 10.31014/aior.1993.03.04.155
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Academic Achievement in Secondary-School Quantitative Economics: Effect of Feedback with Remediation

Abstract: Empirically investigated in this study is the effect feedback with remediation has on academic achievement in quantitative economics among students’ of secondary school. The design of the study was quasi experimental. 164 Senior Secondary 3 (SS3) students offering economics in the three co-educational schools consisted of the study sample. The three schools were purposely selected from Nnewi Education Zone of Anambra State in Nigeria and allocated to 2 experimental groups and 1 control group. Students’ respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…This could be traced to the fact that the mean for male students across the three item formats was higher than their female counterparts. The findings of the current study agree with the position of Thawebieh (2016) that there was a significant difference in the performance of male and female students but disagree with the findings of Eleje et al, [13].…”
Section: Discussion Of Findingscontrasting
confidence: 55%
See 1 more Smart Citation
“…This could be traced to the fact that the mean for male students across the three item formats was higher than their female counterparts. The findings of the current study agree with the position of Thawebieh (2016) that there was a significant difference in the performance of male and female students but disagree with the findings of Eleje et al, [13].…”
Section: Discussion Of Findingscontrasting
confidence: 55%
“…The results of the statistical analysis revealed that there was a significant difference in the performance of students in favour of true-false. Additionally, researchers have equally showed that gender impacts student's academic achievement [13], (Thawebieh, 2016). In this study, the possible effect of gender on students' Economics achievement score in various objective test formats was also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Academic achievement is the presentation results that show the extent to which a student has acquired the specific stated goals of activities in an educational setting (Eleje et al, 2020). As regards Economics, the academic achievement of secondary school students in Economics has been fluctuating over the years.…”
Section: Introductionmentioning
confidence: 99%
“…For students to learn and achieve excellently, especially in the subject that deals with articulation and aggregation, they must be sufficiently and psychologically healthy in behavior [23]. A psychologically healthy individual is the person that has a positive perception of his/her behaviour as it represents the total self.…”
Section: Introductionmentioning
confidence: 99%